Uvedba svetovalnega mentorstva v šolstvo - Cajnko, Petra (Anali PAZU HD, 2022)
In this paper, we present a new learning method, coaching, through which both the lecturer and the student successfully completed the activities that were a prerequisite for achieving the goal. The teaching method was supported by various tools. We also present the results and lessons learnt from the introduction of the three tools into the teaching process. Research based on the use of theories is taken from Slovenian and foreign literature, sourcesand empirical research using statistical methods (two courses: Mathematical modelling and Business economics and management, two years of work: 2019/2020 and 2020/2021). Depending on the time period, the research is retrospective, as it deals with past influences or situations. Based on what has been written, we can conclude that the topic is extremely current, its results will enable lecturers to understand the positive significance in the impact of the introduction of coaching in the field of teaching. The results of the research will enable the institutes to learn about new types of methods that will serve to approximate the activities of coaching in the teaching process.
Keywords: coaching; flow; Mentorstvo (vzgoja in izobraževanje); opravljene naloge; predavatelji; proces izobraževanja; svetovalno mentorstvo; Študenti; task performed; teachers; teaching process; zanos